Ego strength And It’s Relations to Self-Harm among A sample of adolescents Juvenile delinquent and non-delinquent in Homs city - بطيخ لينا ابراهيم; هلال رانيا محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aimed at identifying the relationship between Ego strength and Self-Harm, In addition to and detect differences in both Ego strength and Self-Harm in the light of residence variable (Central Prison - Juvenile Rehabilitation Service - Residence with the family) in a sample of adolescents consisted of (88) juveniles aged between (15-17) years, including (42) juvenile delinquents and (45) juvenile non-delinquents of Al-Farabi high school students in Homs city They were randomly selected. To achieve the objectives of this study To achieve the objectives of the study, the Bar One ego strength scale (Bar On, 1950), Kafafi Arabization (1982), and the self-harm questionnaire were used The results of the study showed that the prevalence of self-harm was higher among juveniles in the central prison by (27.7%), followed by juvenile rehabilitation services (25.92%), followed by juveniles living with parents (23.80%). The results also showed a negative correlation statistically significant between the degrees of self-harm and the degrees of Ego strength, There were no differences in the mean scores on the Ego strength scale and its dimensions among the study sample and also the results revealed that there were significant differences in the average degrees of self-harm in the light of residence variable in favor of juveniles in the interest of rehabilitation of juvenile delinquents.